Application of Integrals in Calculating Ball Volume using GeoGebra - Irvan, Irvan (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
Integral Calculus is a form of mathematics learning that can be applied in everyday life. One application is in calculating the volume of rotating objects. In this research, we combine integral concepts in calculus with the numerical and visualization capabilities provided by GeoGebra software. The aim of this research is to apply the concept of integral calculus in calculating the volume of a rotating object in the form of a ball. The method used is a qualitative descriptive method that uses literature studies to search for formulas and to construct spherical shapes to determine their volume. The experimental method is used to find manual calculation results on real objects. The research results show that the integral concept used in calculating the volume of a ball using software assistance in the form of the GeoGebra application can produce quite accurate results.